Reaction kinetics of versatile peroxidase for the degradation of lignin compounds - Busse, N.; Wagner, D.; Kraume, M.; Czermak, Peter (My University, 2013)
The H[subscript 2]O[subscript 2] dependent degradation of adlerol by a crude versatile peroxidase from Bjekandera adusta, a new ligninolytic enzyme, was investigated. Adlerol (1-(3,4-dimethoxyphenyl)-2-(2-methoxyphenoxy)-1,3-propanediol)) is a non phenolic β-O-4 dimer whose structural architecture represents the most abundant unit (50-65%) of the valuable renewable biopolymer lignin. Lignin removel plays a key role in utilizing lignocellulosic biomass in biorefineries. Steady state analyses in the µL scale showed saturation kinetics for both, H[subscript 2]O[subscript 2] and adlerol with quite sensitive response to H[subscript 2]O[subscript 2]. This was characterized through slow transient states (lag phases) prior steady state and were enhanced by increasing H[subscript 2]O[subscript 2] concentration. The major reason for such phenomena was found to be an accumulation of compound III (E[superscript III]) via reaction of compound II (E[superscript II]) with H[subscript 2]O[subscript 2]; instead with adlerol to the enzymeâ s ground state E[superscript 0] in order to restart another catalytic cycle. As result, the enzyme deviated from its normal catalytic cycle. A corresponding threshold was determined at ≥ 50 μM H[subscript 2]O[subscript 2] and an adlerol to H[subscript 2]O[subscript 2] ratio of 15:1 for the given conditions. Furthermore, E[superscript III] did not represent a catalytical dead end intermediate as it is generally described. By an additional decrease of the adlerol to H[subscript 2]O[subscript 2] ratio of ca. 3 at the latest, considerable irreversible enzyme deactivations occurred promoted through reaction of E[superscript III] with H[subscript 2]O[subscript 2]. At a mL scale deactivation kinetics by H[subscript 2]O[subscript 2] were further examined in dependence on adlerol presence. The course followed a time dependent irreversible deactivation (two step mechanism) and was diminished in the presence of adlerol. The deactivation could be sufficiently described by an equation similar to the Michaelis Menten type, competitive inhibited by adlerol. Finally, first estimates of the kinetic parameters v[subscript max], K[subscript m][superscript S1] (S[subscript 1]: H[subscript 2]O[subscript 2]), K[subscript m][superscript S2] (S[subscript 2]: adlerol), k[subscript i][superscript app] and K[subscript i][superscript app] were made. Moreover, the peroxidase reaction mechanism was reviewed and recommendations are given preventing permature enzyme losses.
Keywords: Versatile peroxidase; Lignin model compound; Steady-state kinetics; Slow transient states; Deactivation